Kedaulatan Rakyat dalam Pemilu dan Pilkada: Antara Idealisme Konstitusi dan Praktik Politik Uang - Mustajib Mustajib (Pemuliaan Keadilan, 2025)
The principle of popular sovereignty is a fundamental foundation of the Indonesian democratic system, as stated in Article 1, Paragraph (2) of the 1945 Constitution. Popular sovereignty emphasizes the importance of the people's right to choose and be chosen in general elections (Pemilu) and regional elections (Pilkada), which serve as the source of legitimacy for a legitimate government. This sovereignty should reflect democratic values that are just and equal. However, in practice, the implementation of popular sovereignty through elections is often tarnished by money politics, which threatens the integrity of democracy itself. This phenomenon indicates a profound distortion of democratic principles, where the election process is more driven by material interests than by political aspirations and ideologies. Money politics not only undermines the quality of elections but also diminishes public trust in the democratic process. This practice allows voters to sell their votes in exchange for money or goods, leading to electoral injustice. It transforms general elections and regional elections from an ideal democratic process into a contest reliant on financial resources, rather than on the quality of the leaders chosen. This article aims to analyze the contradiction between the constitutional ideal of popular sovereignty and the reality of money politics in the administration of general elections and regional elections. This study employs a normative juridical approach with qualitative analysis techniques to explore how current laws have guaranteed the implementation of popular sovereignty. The findings indicate that although the legal framework provides protection for the principle of popular sovereignty, weak law enforcement and the persistent transactional political culture hinder its substantial realization. As a solution, this article recommends several strategic steps, including strengthening regulations to limit money politics, reforming the party system to reduce the dominance of practical politics, and enhancing political education based on democratic values and integrity. With these measures, the principle of popular sovereignty can be more purely and consistently upheld, ultimately strengthening Indonesia’s democratic system to be fair and sustainable.